RANGKAIAN PENYEARAH SETENGAH TERKENDALI TIGA FASA UNTUK PENGENDALIAN KARAKTERISTIK MOTOR ARUS SEARAH SHUNT - Adam, Ahmad Antares (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
A modern control of electric motor’s speed in an industry needs a variable direct voltage. The variable direct voltage can be supplied by semiconductor devices such as SCR. The output voltage of a SCR rectifier depends on the delay angle of the SCR. The aim of this research is to make a SCR rectifier circuit and applying it for observing the characteristics of a shunt direct current motor. The result shows the circuit can work to demonstrate the shunt motor characteristics. Keywords : Rectifier ciscuit, Three phases, Shunt motor, Characteristics.